Strategi Diplomasi Ekonomi Republik Indonesia terhadap Persatuan Emirat Arab tahun 2020-2022 - Tajudin, Muhammad Fadhil Ahadiat; Kaswoto, Junet (Jurnal Informatika Ekonomi Bisnis, 2023)
Economic diplomacy plays a central role for Indonesia in facing inter-state contests at the global level, particularly in political and economic interests. Economic diplomacy in Indonesia garners special attention from the Government of the RI and stands as one of the 4+1 Priorities of Foreign Policy. The Government of RI places emphasis on market expansion in potential non-traditional countries, notably the United Arab Emirates (UAE), with the aim of advancing national interests in the trade, tourism, and investment sectors, alongside optimizing the domestic market at hand. This research focuses on the economic diplomacy strategies employed by the Government of RI concerning the UAE from 2020 to 2022, utilizing insights from the economic diplomacy strategies of developing countries presented by Kishan S. Rana. The methodology employed in this study is qualitative, with primary data acquired through interviews and secondary data garnered through literature review. The research findings demonstrate that the economic diplomacy strategies pursued by the Government of RI towards the UAE align with Rana's conceptual framework, encompassing 4 stages, namely economic salesmanship, networking and advocacy, image building, and regulatory management. The most prominent stage within Indonesia’s economic diplomacy strategy is economic salesmanship, particularly evident through the World Expo 2020 Dubai. Conversely, the stage that exhibits suboptimal perfomance is regulatory management concerning the IUAE-CEPA, which as of the present, has not been ratified by the Government of RI.